The Influence of Good Corporate Governance, Capital Intensity Ratio, and Profitability to Effective Tax Rate (Empirical Study on Manufacturing Companies Basic Industry Sectors and Chemicals Listed In Indonesia Stock Exchange Year 2011-2015) - Anita Wijayanti, Agus Prasetyo, Endang Masitoh & (PROCEEDING ICTESS (Internasional Conference on Technology, Education and Social Sciences), 2018)
This study aims to examine empirically the influence of good corporate governance(independent commissioner, audit committee, board of directors, & audit quality),capital intensity ratio, and profitability to effective tax rate. The population of thisresearch was manufacturing companies basic industry sectors and chemicals listedon the Indonesia Stock Exchange in the period 2011-2015. Sampling was done byusing purposive sampling method. There were 8 companies that fulfilled thecriteria of sampling. This study used multiple linear regression analysis. The resultsof this study showed that the variable of independent commissioner and board ofdirectors significant influence to the effective tax rate. meanwhile variable auditcommittee, audit quality, and capital intensity ratio, and profitability did notsignificant influence to the effective tax rate. Based on the determinationcoefficient test (R2) obtained the coefficient of determination with adjusted R2 of0,300. These result show that 30,0% of variables effective tax rate can be explainedby the independent commissioner, audit committee, board of directors, auditquality, capital intensity ratio, and profitability. While, the rest of 70,0% isexplained by other factors outside the model in this research.Keywords: effective tax rate, independent commissioner, audit committee, board of directors,audit quality, capital intensity ratio, and profitability